Transizione energetica e intelligenza artificiale (Nuovi Autoritarismi e Democrazie: Diritto, Istituzioni, Società (NAD-DIS), 2025)
The contribution reconstructs the topic of artificial intelligence and environment in the context of the interaction between energy transition and digital transition and the European Green Deal. It examines EU Reg.1689/2024 in depth, in terms of definitions and main characteristics, with particular reference to social and environmental well-being.
Keywords: Artificial Intelligence, IA Act, Reg. UE 1689/2024; European Green Deal; energy transition; digital transition